Query Breeding Management Systems (QBMS) R package - Al-Shamaa, Khaled; Crimi, Mariano; Kehel, Zakaria (International Center for Agricultural Research in the Dry Areas, 2023)
Linking data management systems to analytics is an important step in breeding digitalization. Breeders can use this R package to Query the Breeding Management System(s) like BMS, BreedBase, and GIGWA (using BrAPI calls) and help them to retrieve phenotypic and genotypic data directly into their analyzing pipelines developed in R statistical environment.